Extratos naturais de sementes de mamão papaya (Carica papaya L.) e marcela (Achyrocline satureioides) e avaliação da capacidade antioxidante e antimicrobiana em linguiça de frango - Piovesan, Natiéli (2012)
The present study aimed to develop natural extracts from papaya seed (Carica papaya l.) and marcela (Achyrocline satureioides) to be used in chicken sausage, evaluating their antioxidant and anti-microbial activities. Firstly, the hydroethanolic extracts were elaborated and the phenolic compounds characterization and in vitro antioxidant activity were accomplished. Then, the papaya seeds and marcela extracts, in 0,5%, 1%, 1,5% and 0,5 and 0,75% respectively were used in the chicken sausage. The analyses accomplished were: centesimal composition (humidity, protein, ash and fat), pH, objective color, lipid oxidation, microbiological and sensory analyses. The results obtained in the extracts in vitro analyses showed that the marcela extract presents greater amount of total phenolic and higher antioxidant activity compared to the papaya seeds extract. The products centesimal composition complied with the Brazilian law. There was no interference of the extracts addition on the pH of the chicken sausage in relation to the control ones. Regarding color, during the storage period the T2, T3, T4 and T5 treatments presented higher values for h* in relation to control, indicating a color tendency from red to yellow. At the 42 days of storage of the refrigerated chicken sausage, the samples T3 (1,5% ESM) and T5 (0,75%EM) presented the lowest TBARS values, being respectively 0,485 and 0,448 mg malonaldehyde Kg-1 of sample, representing a lipid inhibition higher than control. The values obtained to Clostridium, Staphylococcus positive coagulase; Salmonella and coliforms at 45° were lower than the ones established by law. However the mesophylls aerobic and the psychotropic microorganisms were lower to 10-6 UFC. g-1 up to 21 days of storage, at 4 °C. The mean values of the scores attributed to color, smell, texture and global appearance did not present significant difference (p<0, 05) among the treatments. The acceptability index presented values higher than 70% for all attributes which is considered good. Then, it is possible to conclude that the addition of papaya seeds (1,5%) and marcela (0,75%) extracts can be used in the chicken sausage manufacture since they have presented antioxidant capacity and may lengthen this meat product s shelf life.